Preparation and Characterization of Double-Layered Microcapsules Containing Nano-SiO2 - Xue Sun; Jingcheng Su; Rui Zhang; Fangyu Fan (International Journal of Polymer Science)
The double-layered microencapsulation technology has been used in many fields. In this study, the double-layered microencapsulated anthocyanin of Passiflora edulis shells (APESs) was prepared via complex coacervation using gelatin and gum Arabic as the first wall materials (single-layered microcapsules (SMs)) and using gum Arabic containing nano-SiO2 as the second wall material (double-layered microcapsules (DMs)/nano-SiO2) to enhance the stability of the core material. Properties of microcapsules were analyzed on the basis of EE, morphology, scanning electron microscopy (SEM), droplet size, moisture content, and differential scanning calorimetry (DSC). The results showed that the EE values of SMs, DMs, and DMs/nano-SiO2 were 96.12%, 97.24%, and 97.85%, respectively. DMs/nano-SiO2 had the lowest moisture content (2.17%). The average droplet size of DMs/nano-SiO2 (34.93 μm) was higher than those of SMs and DMs. DSC indicated that the melting temperature of DMs/nano-SiO2 was 73.61°C and 45.33°C higher than those of SMs and DMs, respectively. SEM demonstrated that DMs/nano-SiO2 had the smoothest surface compared with the other two kinds of microcapsules. The storage stability of APESs and their microcapsules indicated that the stability of the microcapsules was improved by adding DMs/nano-SiO2 into the wall material of microcapsules. These results indicated double-layered microcapsules containing silica nanoparticles contribute to the stability of the core material.